Correction: Assessment of psychological terror and its impact on mental health and quality of life in medical residents at a reference medical center in Mexico: A cross-sectional study. - Víctor Manuel Enriquez Estrada; Neftali Eduardo Antonio-Villa; Omar Yaxhemen Bello-Chavolla; Carlos Fredy Cuevas-García; Pedro Luis Vargas Gutiérrez; Irma Sau-Yen Corlay Noriega; Luis Rey García-Cortés (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0295138.].